2016
DOI: 10.1111/1755-5922.12161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mini‐Tyrosyl‐tRNA Synthetase/Mini‐Tryptophanyl‐tRNA Synthetase on Angiogenesis in Rhesus Monkeys after Acute Myocardial Infarction

Abstract: contributed equally and are co-first authors. SUMMARYAims: The purpose of this study was to clarify the effect of mini-tyrosyl-tRNA synthetase/ mini-tryptophanyl-tRNA synthetase (mini-TyrRS/mini-TrpRS) in ischemic angiogenesis in rhesus monkeys with acute myocardial infarction (AMI). Methods: A 27-gauge needle was incorporated percutaneously into the left ventricular myocardium of rhesus monkeys with AMI. All monkeys were randomized to receive adenoviral vector mini-TyrRS/mini-TrpRS, which was administered as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Forward genetic screens conducted in zebrafish have linked iars1, sars1, and tars1 variants to defects in angiogenesis during development, which can also be induced through morpholino knockdown of the respective genes ( Jin et al, 2007 ; Fukui et al, 2009 ; Herzog et al, 2009 ; Cao et al, 2016 ; Castranova et al, 2016 ; Wang K et al, 2018 ), but not through general inhibition of protein synthesis ( Fukui et al, 2009 ; Herzog et al, 2009 ; Xu et al, 2012 ; Cao et al, 2016 ). Pro- and anti-angiogenic effects of TyrRS and TrpRS splice variants via the phosphoinositide 3-kinase (PI3K) and extracellular signal-regulated kinase (ERK) pathways have also been demonstrated in vivo in rats and rhesus monkeys ( Wang et al, 2016 ; Zeng et al, 2016 ). Additionally, a Wars2 variant identified through linkage analysis impairs cardiac angiogenesis in rats, and wars2 knockdown in zebrafish causes similar vascularization defects ( Wang et al, 2016 ).…”
Section: Animal Model Systems For Studying Recessive Ars Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Forward genetic screens conducted in zebrafish have linked iars1, sars1, and tars1 variants to defects in angiogenesis during development, which can also be induced through morpholino knockdown of the respective genes ( Jin et al, 2007 ; Fukui et al, 2009 ; Herzog et al, 2009 ; Cao et al, 2016 ; Castranova et al, 2016 ; Wang K et al, 2018 ), but not through general inhibition of protein synthesis ( Fukui et al, 2009 ; Herzog et al, 2009 ; Xu et al, 2012 ; Cao et al, 2016 ). Pro- and anti-angiogenic effects of TyrRS and TrpRS splice variants via the phosphoinositide 3-kinase (PI3K) and extracellular signal-regulated kinase (ERK) pathways have also been demonstrated in vivo in rats and rhesus monkeys ( Wang et al, 2016 ; Zeng et al, 2016 ). Additionally, a Wars2 variant identified through linkage analysis impairs cardiac angiogenesis in rats, and wars2 knockdown in zebrafish causes similar vascularization defects ( Wang et al, 2016 ).…”
Section: Animal Model Systems For Studying Recessive Ars Diseasesmentioning
confidence: 99%
“…Pro-and anti-angiogenic effects of TyrRS and TrpRS splice variants via the phosphoinositide 10. 3389/fnins.2023.1182874 Frontiers in Neuroscience 12 frontiersin.org 3-kinase (PI3K) and extracellular signal-regulated kinase (ERK) pathways have also been demonstrated in vivo in rats and rhesus monkeys (Wang et al, 2016;Zeng et al, 2016). Additionally, a Wars2 variant identified through linkage analysis impairs cardiac angiogenesis in rats, and wars2 knockdown in zebrafish causes similar vascularization defects (Wang et al, 2016).…”
Section: Animal Models To Investigate Secondary Ars Functionsmentioning
confidence: 99%
“…Our findings showed that the level of this protein decreases in the acute phase of ischemic stroke. It is commonly observed that at the same conditions there is an increased expression of another form of this enzyme, mini-TrpRS, which impairs myocardial perfusion after infarction in rat [75] and in monkeys [76]. As an antagonist of ocular angiogenesis, it may also have a beneficial effect in inhibiting pathological neovascularization [77].…”
Section: Proteomics Analysismentioning
confidence: 99%